The tetraspanin protein CD37 regulates IgA responses and anti-fungal immunity. - Annemiek B van Spriel (Public Library of Science (PLoS), 2009)
Immunoglobulin A (IgA) secretion by plasma cells in the immune system is critical for protecting the host from environmental and microbial infections. However, the molecular mechanisms underlying the generation of IgA(+) plasma cells remain poorly understood. Here, we report that the B cell-expressed tetraspanin CD37 inhibits IgA immune responses in vivo. CD37-deficient (CD37-/-) mice exhibit a 15-fold increased level of IgA in serum and significantly elevated numbers of IgA(+) plasma cells in spleen, mucosal-associated lymphoid tissue, as well as bone marrow. Analyses of bone marrow chimeric mice revealed that CD37-deficiency on B cells was directly responsible for the increased IgA production. We identified high local interleukin-6 (IL-6) production in germinal centers of CD37-/- mice after immunization. Notably, neutralizing IL-6 in vivo reversed the increased IgA response in CD37-/- mice. To demonstrate the importance of CD37-which can associate with the pattern-recognition receptor dectin-1-in immunity to infection, CD37-/- mice were exposed to Candida albicans. We report that CD37-/- mice are evidently better protected from infection than wild-type (WT) mice, which was accompanied by increased IL-6 levels and C. albicans-specific IgA antibodies. Importantly, adoptive transfer of CD37-/- serum mediated protection in WT mice and the underlying mechanism involved direct neutralization of fungal cells by IgA. Taken together, tetraspanin protein CD37 inhibits IgA responses and regulates the anti-fungal immune response.